New Energy Technology Brings Benefits To Human Society -Take New Energy Vehicles As An Example - lyu, lingbo (International Journal of Management and Education in Human Development, 2022)
In today's society, in the context of people's increasing need for a better quality of life and the limited total amount of natural resources and increasingly prominent environmental problems. The contradiction between the increase of global automobile demand and environmental protection and resource conservation is becoming more and more prominent. The development of new energy vehicle technology provides a very reliable path to reconcile this contradiction. The development of new energy vehicle technology not only guides the development direction of new energy vehicles, but also indirectly affects the development of many social factors such as system, environment and economy. The academic community has mostly studied the development of new energy vehicle technology from the economic or technological perspectives, and there are fewer philosophical reflections on the development of this technology. In view of this, this paper hopes to deeply reflect on the development of new energy vehicle technology and its social impact from a philosophical perspective. The development of new energy vehicle technology has multiple attributes of society, science and technology, and economy. This paper will analyze the development of new energy vehicle technology in order to promote the sustainable development of society, the synergistic development of science and technology, and the improvement of China's international competitiveness.